Evaluating the effects of exclusive bus lanes on passenger ridership and travel time in Kuala Lumpur city roads - Meliti, Samira; Kadar Hamsa, Abdul Azeez (Eastern Asia Society for Transportation Studies, 2011)
Bus priority treatment in urban areas is seen as an effective measure to improve bus transit services. This paper describes the effects of exclusive bus lanes on passenger ridership and travel time. Exclusive bus lanes along Jalan Tuanku Abdul Rahman (Jalan TAR) and Jalan Syed Putra (Jalan SP) are used to measure the service characteristics of bus transit. Passenger ridership and travel time survey were conducted during peak and off peak-hours on weekdays and weekend. The differences between mean travel time of buses and motorcars were statistically tested by using T-test. The findings showed that the bus passenger ridership is generally low and the effect of exclusive bus lanes on passenger ridership is insignificant. Travel time for buses along exclusive bus lanes was found significantly higher than other traffic (especially motorcars) along adjacent traffic lanes. Recommendations are drawn to overcome issues confronting exclusive bus lanes in Kuala Lumpur.